A Novel Asymmetric Multilevel Inverter with Reduced Number of Switches for Grid-tied Solar PV System - Siva, Asapu; Rajendran, Vanitha (Recent Advances in Electrical & Electronic Engineering, 2022)
Background & Objective: In single-phase solar PV applications, the module voltage level is limited; therefore, a coupled step-up transformer is a mandatory portion to interconnect into the grid. However, due to the presence of a transformer, the overall cost and size of the single-phase grid-tied solar PV system are higher. A multilevel inverter is an alternative solution to solve these issues, but it requires more switches. Methods: In order to overcome this drawback, this particular paper proposes a novel Asymmetric Multilevel Inverter (AMLI) with a reduced number of switches for a solar PV grid-tied system. The operational details of the proposed converter are explained in this paper. In addition, the MPPT control has been implemented in the proposed novel AMLI and presented in this paper. The hysteresis current control mechanism is applied to the proposed converter and corresponding control blocks are reported in this paper. Results: Finally, to validate the proposed system, the simulation results are performed and correlated with a theoretical approach. Furthermore, to verify the feasibility of proposed converter for solar PV grid-tied system, the experimental setup was made, and experimental results have been measured and presented in this paper. Conclusion: From the measured results, it is concluded that the proposed asymmetric MLI can be the most promising converter for solar PV grid-connected systems.
Keywords: hysteresis current control